HappyTap: Encouraging handwashing in rural Vietnam - CHIDAMBARAM, Ravi (Institutional Knowledge at Singapore Management University, 2015)
The case is set in Phnom Penh in March 2014. Geoff Revell was the Regional Programme Manager of WaterSHED, a non-governmental organisation (NGO) based in Phnom Penh, Cambodia, founded in August 2011. WaterSHED had been established to promote socially impactful business in water, sanitation, and hygiene in developing countries in Asia. The HappyTap project, which was rolled out in Vietnam in 2011, was one such initiative under WaterSHED’s umbrella to help promote handwashing in rural areas of developing countries. The HappyTap was a handwashing device that came with its own water tank, and hence had no need for running water, and could be easily placed in households to encourage handwashing at home. To fund the commercialisation of the HappyTap, Revell had applied to the Development Innovation Ventures (DIV), a three-stage scheme offered by the United States Agency for International Development (USAID). Rollout of the HappyTap through direct and indirect marketing channels had been slower than planned. Revell had recently signed a contract with the Women’s Union, a quasi-governmental organisation in Vietnam to organise sales events to promote the HappyTap. However, he recognised that he needed to make longer-term strategic decisions on the business model, so that the HappyTap enterprise could be sustainable and scalable. Should he consider more avenues for funding going forward, instead of depending only on USAID? Should he look towards other marketing channels like exports?